2014
DOI: 10.1007/s11145-014-9520-5
|View full text |Cite
|
Sign up to set email alerts
|

Levels of phonology related to reading and writing in middle childhood

Abstract: The relationships of different levels of phonological processing (sounds in heard and spoken words for whole words, syllables, phonemes, and rimes) to multi-leveled functional reading or writing systems were studied. Participants in this cross-sectional study were students in fourth- grade (n=119, mean age 116.5 months) and sixth- grade (n=105, mean age 139.7 months). Multiple Indicators and Multiple Causes (MIMIC) modeling was used to analyze whether different levels of sound processing in heard and spoken wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Research (e.g., Engen & Høien, 2002; Snowling & Nation, 1997) also suggests that phonological awareness contributes to reading comprehension. In a study looking at other aspects of reading (Del Campo, Buchanan, Abbott, & Berninger, 2015), phonological processing (phonology for whole words and phonemes) explained unique variance in fourth and sixth graders’ reading levels.…”
Section: Phonological Processingmentioning
confidence: 99%
“…Research (e.g., Engen & Høien, 2002; Snowling & Nation, 1997) also suggests that phonological awareness contributes to reading comprehension. In a study looking at other aspects of reading (Del Campo, Buchanan, Abbott, & Berninger, 2015), phonological processing (phonology for whole words and phonemes) explained unique variance in fourth and sixth graders’ reading levels.…”
Section: Phonological Processingmentioning
confidence: 99%
“…Findings on phonological awareness have shown that this is a key skill in the early years of a child's schooling. Many studies have confirmed that this skill is a good predictor of future reading performance (Porta et al, 2010; Suárez et al, 2013; Kjeldsen et al, 2014; Del Campo et al, 2015). Alphabetic knowledge refers to the knowledge of the rules for grapheme-phoneme (G-P) and phoneme-grapheme (P-G) conversion; fluency, which is described as the ability to read texts rapidly and accurately, using appropriate intonation within the reading context; vocabulary, i.e., learning the meaning and use of words in a given context; and comprehension, which refers to a child's ability to reason about, reflect on, and understand what they are reading (Jiménez et al, 2012).…”
Section: Evidence-based Practices For Teaching Readingmentioning
confidence: 92%
“…Between the two factors in phonological awareness, phonemic awareness correlated higher with reading comprehension ( r = .39) than did syllable awareness ( r = .06). Del Campo and colleagues (2015) showed that all sound-unit factors measured by phoneme, rime, syllable, and words were significantly interrelated; word and phoneme units explained unique variance of reading comprehension in both 119 fourth- and 105 sixth graders.…”
Section: Introductionmentioning
confidence: 96%
“…Assessing these tasks is not necessarily discrete. Additionally, grade-level differences were found in phonological units as a predictor of literacy (Del Campo, Buchanan, Abbott, & Berninger, 2015).…”
Section: Introductionmentioning
confidence: 99%